2018
DOI: 10.1071/fp17301
|View full text |Cite
|
Sign up to set email alerts
|

Roles of hydrogen gas in plants: a review

Abstract: Hydrogen gas (H2) was first identified as a unique molecular messenger in animals. Since H2 was reported as a novel antioxidant, it has been proven effective in treating many diseases. However, the studies concerning H2 in plants are just beginning to emerge. Here, two paths of H2 production in plants have been reported, namely, hydrogenase and nitrogenase. H2 has positive effects on seed germination, seedling growth, adventitious rooting, root elongation, harvest freshness, stomatal closure and anthocyanin sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…Molecular hydrogen (H 2 ) is suggested to be a bioregulator in plant defence against environmental stresses [6,43]. Previous work has documented the role of H 2 in plants coping with Cd.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular hydrogen (H 2 ) is suggested to be a bioregulator in plant defence against environmental stresses [6,43]. Previous work has documented the role of H 2 in plants coping with Cd.…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate, Kanno et al [ 63 ] inoculated seedlings of Oryza sativa and Arabidopsis thaliana with streptomyces and found that the bacteria were taken into the plant tissues and that their H 2 oxidizing activity continued. Likewise, treatment of soils with H 2 can alter the populations of microorganisms which may be found there [ 2 ], and this can also have an influence on plant growth.…”
Section: Influence Of Bacteria On Hydrogen Availability To Plantsmentioning
confidence: 99%
“…H 2 is involved in a range of physiological responses in plants, which is one of the reasons why it has been proposed to be a useful tool for agriculture [ 20 ]. As only some highlights are discussed here, an in-depth review by Li et al [ 2 ], which focusses on the multiple roles of H 2 within plant systems is recommended.…”
Section: H 2 Effects On Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…[31] Hydrogen gas (H 2 ), mainly catalyzed by hydrogenase and nitrogenase in plants, has recently been identified as a gasotransmitter. [32] A large number of studies have shown that exogenous application of H 2 (hydrogen-rich water; HRW) can influence multiple plant responses, including the alleviation of various abiotic stress and the promotion of root development. [33][34][35][36] In addition, the application of H 2 has been observed to prolong the storage life of fruits and flowers.…”
Section: Introductionmentioning
confidence: 99%